Dietary Fats Are Vital For Human Long-Term Health: Pharmaceutical Science-Pharmacy practice for good health promotion - Sumathy.T; Maheshkumar V.P; Jaikumar.S (International Journal of Life Science and Pharma Research, 2022)
Lipids are the major contributors of taste, texture and energy of a diet. Changes in the intake of dietary fats bring about varied serum cholesterol levels as well the other factors that cause risk of chronic diseases. It has been established over years that the risk of CAD and other chronic health problems are not significantly influenced by the dietary saturated fatty acids (SFAs). Many recent researches also reported that the SFAs present in dairy products and coconut oil are very helpful in improving the health of an individual. Even though enhancement of inflammation and augmentation of the chronic ailments by V6 polyunsaturated fatty acids (PUFAs) have been reported widely, the V3 PUFA’s take the other side and act to counter the ill effects. Obesity and other associated health issues arise mainly due to the use of diets rich in carbohydrates instead of saturated fats. The benefits of replacing these carbohydrates and others with alternative nutrients have been well established with known mechanisms which bring down the adverse effects. The quality of fat may bring about chronic degenerative effects in the later stages. The use of fat and its types is shifted towards a pattern of healthy diet wherein the food may include a variety of different fats even at high levels. The present scenario of the researches in public health is mainly centered with the analysis of the association between dietary fat, level and quality, its impact on the risk of chronic diseases and cure. Thus, this review focuses on the need to re-examine the use of dietary fats and their clinical implications.